The Effect of Using Video Tutorial Learning Media on Students’ Learning Outcomes in Physical Education Subjects of Football for Class VIII SMP Angkasa Lanud Padang - Ulyas, Muhammad Rhavi Ramadhion; Bentri, Alwen; Eldarni, Eldarni; Supendra, Dedi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was carried out with the aim of describing whether there was an effect of the use of video tutorial learning media on student learning outcomes in the physical education subject of football for class VIII SMP Angkasa Lanud Padang.The method in this research uses a quantitative approach using pre-experimental methods. Data collection techniques use test and documentation techniques. And the data analysis techniques used in this research are validity test, reliability test, mean, standard deviation, variance, normality test, homogeneity test, and hypothesis test.The conclusion of this research is that based on data analysis and discussion of research results, it can be found that student learning outcomes when given treatment are higher than learning outcomes before being given treatment. So, the use of video tutorial media in the learning process has a significant effect on the learning outcomes of students in physical education subjects of football for class VIII SMP Angkasa Lanud Padang.